Quantitative detection and characterization of Shiga toxin-producing Escherichia coli O157 and non-O157 in raw vegetables by MPN-PCR in Malaysia - Loo, Yuet Ying; Soopna, Puspanadan; Goh, Sur Guat; Kuan, Chee Hao; Chang, Wei San; Lye, Ying Ling; Tang, John Yew Huat; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Foodborne diseases are mainly caused by bacterial contamination which can lead to severe diarrhea. This study aimed to detect the presence of Shiga toxin-Producing Escherichia coli O157, Escherichia coli non-O157 and virulence gene in raw vegetables. The samples were purchased from wet market and hypermarket in Selangor. The detections were carried out by using the combination methods of Most Probable Number-Polymerase Chain Reaction (MPN- PCR). A total of 37(18.5%) samples were found to be contaminated by STEC. Out of these 37 isolates, four (10.8%) of the isolates were E. coli O157 while 33(89.2%) were E. coli non- O157. However, there was no E. coli O157:H7 detected in all the samples. The occurrence of Shiga toxin-Producing E. coli in edible raw vegetables samples suggests the importance of this pathogen in vegetables. Therefore, more studies are required to remove this pathogen from vegetables.